2017
DOI: 10.3390/molecules22091481
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Extraction of Natural Antioxidants from the Exotic Gordonia axillaris Fruit: Optimization and Identification of Phenolic Compounds

Abstract: Our previous study reported that the fruit of Gordonia axillaris, an edible wild fruit, possessed strong antioxidant activity. In this study, a microwave-assisted extraction (MAE) method was established to extract antioxidants from the fruit of Gordonia axillaris. The influence of five parameters, including ethanol concentration, solvent/material ratio, extraction time, extraction temperature and microwave power, was investigated by single-factor experiments. Three factors, namely ethanol concentration, solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 59 publications
2
55
1
2
Order By: Relevance
“…In addition, the analysis of the residues generated between the predicted values and the observed values, the coefficient determination value (0.9448) and adjust coefficient of determination value (0.8988) indicated a good predictability of the model. Li et al ( 2017 ) established a microwave-assisted extraction (MAE) method to extract antioxidants from the fruit of Gordonia axillaris, and the method was compared with two conventional methods (Soxhlet extraction and maceration extraction). The antioxidant capacity of the extract determined by MAE was stronger than those obtained by Soxhlet extraction (114.1 ± 2.0 μmol Trolox/g DW) or maceration (168.7 ± 3.9 μmol Trolox/g DW) (Li et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the analysis of the residues generated between the predicted values and the observed values, the coefficient determination value (0.9448) and adjust coefficient of determination value (0.8988) indicated a good predictability of the model. Li et al ( 2017 ) established a microwave-assisted extraction (MAE) method to extract antioxidants from the fruit of Gordonia axillaris, and the method was compared with two conventional methods (Soxhlet extraction and maceration extraction). The antioxidant capacity of the extract determined by MAE was stronger than those obtained by Soxhlet extraction (114.1 ± 2.0 μmol Trolox/g DW) or maceration (168.7 ± 3.9 μmol Trolox/g DW) (Li et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…At above 60°C, the extraction rate began to decline. Due to the fact that low temperature dose not facilitate the diffusion of molecules, leading to the incompletion of extraction, while high temperature is prone to cause the degradation of bioactive constituents, both of which can induce the decrease of extraction yield (Ya et al, 2017).…”
Section: Effects Of Extraction Temperature On Extraction Rate Of Tfcmkmentioning
confidence: 99%
“…However, too much temperature increment at higher MAE power causes a thermal degradation of kaempferol, hence reducing its yield. Li et al [27] also found that excessive microwave power causes the degradation of some antioxidants, and hence adversely affecting the extraction yield. The highest kaempferol yield (21.55 mg/g DW) from C. alata was achieved at microwave power of 100 W.…”
Section: Effect Of Mae Power and Time On Polyphenol Extractionmentioning
confidence: 99%